2011
DOI: 10.2514/1.48056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Longitudinally Forced, Bluff Body Stabilized Flame

Abstract: This paper describes an investigation of the response of bluff body stabilized flames to harmonic oscillations. This problem involves two key elements: the excitation of hydrodynamic flow instabilities by acoustic waves, and the response of the flame to these harmonic flow instabilities. In the present work, data were obtained with inlet temperatures from 297 to 870 K and flow velocities from 38 to 170 m=s. These data show that the flame-front response at the acoustic forcing frequency first increases linearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For this reason, the perturbation velocity is modelled as a travelling wave that originates at the burner lip (Ducruix, Durox & Candel 2000;Preetham, Hemchandra & Lieuwen 2008;Kashinath et al 2013b). Experiments on laminar premixed flames (Boyer & Quinard 1990;Baillot et al 1992;Durox, Schuller & Candel 2005;Birbaud, Durox & Candel 2006;Kornilov, Schreel & de Goey 2007;Karimi et al 2009;Shanbhogue et al 2009) and turbulent premixed flames (Shin et al 2011;O'Connor & Lieuwen 2012), and direct numerical simulations (DNS) in our previous work (Kashinath et al 2013b), have shown that the phase speed of these velocity perturbations is not equal to the mean flow velocity. It is a function of the forcing frequency but is independent of the forcing amplitude.…”
Section: Reduced-order Model Of the Perturbation Velocity Fieldmentioning
confidence: 98%
“…For this reason, the perturbation velocity is modelled as a travelling wave that originates at the burner lip (Ducruix, Durox & Candel 2000;Preetham, Hemchandra & Lieuwen 2008;Kashinath et al 2013b). Experiments on laminar premixed flames (Boyer & Quinard 1990;Baillot et al 1992;Durox, Schuller & Candel 2005;Birbaud, Durox & Candel 2006;Kornilov, Schreel & de Goey 2007;Karimi et al 2009;Shanbhogue et al 2009) and turbulent premixed flames (Shin et al 2011;O'Connor & Lieuwen 2012), and direct numerical simulations (DNS) in our previous work (Kashinath et al 2013b), have shown that the phase speed of these velocity perturbations is not equal to the mean flow velocity. It is a function of the forcing frequency but is independent of the forcing amplitude.…”
Section: Reduced-order Model Of the Perturbation Velocity Fieldmentioning
confidence: 98%
“…For example, past studies have defined the flame position with respect to the axial coordinate [13,14], transverse coordinate [2,3,8] or in a coordinate system normal to the time averaged flame position [7,9,15]. To illustrate, the resulting expression written in the axial coordinate system is: (2) Here, x A ≡ x A (x, z, t).…”
mentioning
confidence: 99%
“…Shin et al [13] and Shanbhogue et al [14] used the axial coordinate system for their study, as the position of shallow angle flames remains a single valued function of the coordinate for much larger amplitudes in that coordinate system. We focus attention for the rest of this note on the linearized flame area dynamics.…”
mentioning
confidence: 99%
“…As experimental chemical luminescence images illustrated [12] , the flames did not directly attach to the bluff body. According to the theory of flame propagation, anchoring points are essential for flame existence.…”
Section: Introductionmentioning
confidence: 92%